MANAGEMENT FISIOTERAPI PADA KASUS LOW BACK PAIN EC HERNIA NUCLEUS PULPOSUS DI RSUP Dr SARJITO YOGYAKARTA: CASE REPORT - Atmaja, Ferlina Fidya; Isnaini Herawati; Kuwadi, Kuwadi (Journal of Innovation Research and Knowledge, 2023)
Background: Low back pain often occurs in middle age, namely between 45-65 years. Where one of the causes of low back pain is due to trauma or improper body position when bending so that over time it can cause a Hernia Nucleus Pulposus (HNP). HNP itself is a condition where the nucleus pulposus comes out and protrudes, which then presses towards the spinal canal through the torn annulus fibrosus. In Indonesia, the prevalence of HNP has not been specifically stated, but the prevalence of joint disease increases significantly at the age of more than 45 years. Objective: To know the physiotherapy management using the ir, tens, and exercise therapy methods (core exercise) in cases of low back pain ec hernia nucleus pulposus L5-S1. Methods: Research using the Case Report method conducted at Dr Sarjito General Hospital Yogyakarta in a 62 yearold female patient diagnosed with physiotherapy for low back pain ec hernia nucleus pulposus L5-S1 with complaints of easy aches and pain from the lower back radiating to the legs. Patients were given interventions in the form of ir, tens, and exercise therapy (core exercise) which was done once a week. Results: Physiotherapy modalities in the form of IR, TENS, and Exercise Therapy in the form of Core Exercise are able to reduce muscle spasms, tenderness and motion pain, increase range of motion of joints, and increase in functional activity. Conclusion: Based on this study using the Case Report, it shows that physiotherapy management with the exercise therapy method in cases of low back pain ec hernia nucleus pulposus L5-S1, as a whole, the evaluation results obtained showed an improvement.